Relationship between management and field performance of draught animals used for land preparation: An example from South Kordofan State, Sudan - Elsamawal Khalil Makki; Abu-Elgasim Manzool (Global Journal of Plant and Soil Sciences, 2023)
This study was conducted to investigate the association between animal work hours, feeding and other aspects of animal management and care on the field capacity and efficiency recorded by these working animals in Adilling, South Kordofan State, Sudan. The study followed the cross-sectional survey design with a sample of 100 farmers from 10 villages in the locality following the systematic random sampling technique based on geographical location. Data were collected using a formal survey questionnaire in a face to face interview, for literacy reasons, combined with direct field measurements during land preparation. The results revealed that field capacity was significantly related to veterinary care of draught animals (p= 0.001), while the effect of daily work hours and type of animal feed was not significant. Farmers’ status and financial capacity, as expressed by their production, purpose significantly affected field capacity and efficiency (p = 0.033 and p = 0.021, respectively) with 64% of those producing cash crops working at 0.02 – 0.08 ha/h. The majority of the latter group (78%) recorded field efficiencies between 70 and 90%.